Left atrial strain and compliance in the diagnostic evaluation of heart failure with preserved ejection fraction. (28th March 2019) - Reddy, Yogesh N.V.; Obokata, Masaru; Egbe, Alexander; Yang, Jeong Hoon; Pislaru, Sorin; Lin, Grace; Carter, Rickey; Borlaug, Barry A.
Abstract : Aims: Left atrial (LA) function is impaired in heart failure with preserved ejection fraction (HFpEF) and predicts disease severity and risk of adverse outcome. We sought to evaluate whether LA strain could enhance diagnosis of HFpEF. Methods and results: Consecutive patients with unexplained exertional dyspnoea and image quality suitable for measuring LA strain underwent invasive cardiopulmonary exercise testing to ascertain the presence of HFpEF or non‐cardiac causes of dyspnoea (NCD). LA reservoir strain was measured in all patients, while LA conduit and booster strain were measured in patients with sinus rhythm. LA strain was measurable in 363 of 378 examinations (96.5%; HFpEF: 238, NCD: 125). LA reservoir strain (29 ± 16% vs. 40 ± 13%, P  < 0.0001) and conduit strain (18 ± 10% vs. 22 ± 10%, P  = 0.0001) were significantly impaired in HFpEF compared to NCD. Of all echocardiographic indices, LA reservoir strain best discriminated HFpEF from NCD [area under the curve (AUC) 0.719, P  < 0.0001], outperforming E/e' (AUC difference +0.117, P  < 0.0001), LA enlargement (+0.090, P  = 0.001), tricuspid regurgitation velocity > 2.8 m/s (+0.082, P  = 0.0085), left ventricular hypertrophy (+0.0159, P  < 0.0001) and left ventricular global longitudinal strain (+0.0198, P  < 0.0001). Indexing LA reservoir strain to estimated LA pressure (E/e') as a surrogate for LA compliance further improved diagnostic performance (AUC 0.772, P  < 0.0001; +0.053 compared to LA reservoir strain alone, P  = 0.003). Conclusion: Left atrial reservoir strain may provide enhanced diagnostic accuracy beyond conventional echocardiographic measures to discriminate HFpEF from NCD. Further study is required to verify the diagnostic utility of LA strain.